The Histological Features of Schwannoma in Frozen Section: A Case Report - Safnita, Dewi; Mulyani, Henny (Frontiers on Healthcare Research, 2024)
Background: Intraoperative diagnosis by cytological and frozen section procedures is needed in some cases including peripheral nerve specimens. The results of the cytological evaluation and frozen sections can be relied upon to guide the surgeon in making intraoperative decisions. The pathologist provides information on gross and microscopic findings that correlate with the clinical, and radiological. Although the cytology and frozen section diagnosis approach has been carried out in a multidisciplinary manner, there are still limitations in the intraoperative diagnosis of peripheral nerve specimens. Limitations in this procedure can be overcome by understanding and analyzing possible errors and pitfalls during the procedure thereby increasing the accuracy of the diagnosis. Case report: Schwannoma is a nerve sheath tumor consisting of neoplastic cells with Schwann cell differentiation that generally originates from peripheral nerves in the skin and subcutaneous tissue of the head and neck or along the flexor surfaces of the extremities. More than 90% of schwannomas are solitary and sporadic lesions that can affect any age but with a peak incidence in the fourth to sixth decades of life and there is no racial or gender predisposition. Conclusion: Schwannomas often appear as asymptomatic masses or incidental findings. Intraoperative frozen section pathological diagnosis can be used in determining subsequent surgical management.